LOKAKARYA KEPEMIMPINAN KEPALA SEKOLAH LUAR BIASA (SLB) - Nia Wahyu Damayanti; Bambang Winarto; Abdul Hamid Bachtiar (PT. Gelora Cipta Nusantara, 2023)
Workshop activities is a means of strengthening the leadership of extraordinary school principals. This activity aims to provide an overview of the principal's leadership pattern in the form of a leadership workshop addressed to the Principal of Special Schools. This workshop also aims to improve the quality of inclusive education in special schools which focuses on the role of the principal as the main leader. The service method used is in the form of joint activity forums involving school facilitators and special school principals. Workshops are carried out by holding training sessions for presentation of material, group discussions, questions and answers, and sharing of good practices aimed at developing an understanding of effective leadership in the educational context in principals are actively involved in the workshop process to share experiences, challenges, and their efforts in build an educational environment. This workshop demonstrated that extraordinary school principals play a major role in leading and directing education in their schools. The principal as a leader is a liaison between teachers, students, parents and the community in an effort to create a child-friendly environment. These workshops provide an opportunity for school principals to develop leadership skills in special schools, such as effective communication, wise decision-making, and the ability to motivate and inspire teams in schools. This workshop was the initial initiation of school principals to collaborate with each other to mutually build education in Special Schools.